EFL Teachers’ Perceptions: Challenges and Coping Strategies of Integrated Skills Approach (ISA) Implementation at Senior High Schools in Aceh - Saiful Akmal; Yuliar Masna; Mutiara Tria; Titin Arifa Maulida (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2020)
Integrated Skills Approach (henceforth ISA) is valuably considered to practice all language skills simultaneously with wide and various activities offered to expose learners to the real communicative purpose. This research aims to find out teachers’ perceptions of challenges and coping strategies in implementing ISA at their respective schools. The research participants were chosen by using purposive sampling, in which the information towards six English teachers from different Senior High School in Banda Aceh and Aceh Besar by using unstructured interviews. The findings revealed that generally, most teachers had positive perceptions towards ISA. Only one teacher’s face constrains in applying ISA. Furthermore, the teachers also faced challenges in applying integrated skills approach in the classroom, those are; students’ lack of vocabulary, school environment and facilities, and teachers’ difficulties in designing activity/material. Nevertheless, the teachers have their strategies to cope with those challenges such as; enriching vocabulary through flashcards, grouping students randomly, preparing their own material and equipment, motivating them by giving interesting short movies and games and expanding their knowledge more about integrated skills approach.